(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the formation of the Khwarazmian state in the 12th–13th centuries, the process of gaining political independence, and the key characteristics of Ala al-Din Muhammad’s reign. It is shown that the decline of the Seljuk Empire provided the Khwarazmshahs with opportunities for independent actions, while their diplomatic and military strategies influenced the geopolitical situation in the region. The reign of Ala al-Din Muhammad is considered the peak of the Khwarazmian Empire, as his military campaigns led to the annexation of Khorasan, Transoxiana, and the territories of the Ghaznavids. Additionally, his relations with the Qara Khitai and political decisions are analyzed.